Malang Mask Puppet in Era of Globalization: Social and Cultural Impact - Wibowo, Arining (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2019)
This article discusses socio and cultural impact as an effect of the commercialization of Malang mask puppet in the era of globalization. Padepokan Seni Asmoro Bangun located at Kedungmonggo Hamlet Malang Regency modifies the art of Malang mask puppet in order to turn the function of traditional art from ritual to the commodity. This research method is qualitative by using observation, interviews, and documentary studies for data collection. The result shows that modification creates three impacts, social and cultural impacts, also the occurrence of new senses in terms of Malang mask puppet includes creativity, prosperity, education, aesthetic, conservation, and identity sense.Ã‚Â